Health Literacy in Preventing Bullying Behavior among Students at SMP Negeri 2 Balocci - Resky, Nur; Suriah, Suriah; Syam, Rizky Chaeraty; Humairah, Rahma; Faisal, Dania Rifqah Maharani; Ikadiana, Futri Amelia; Patilangi, Kezia Batara; Bali, Nurahma Azizah A. (Yayasan Mestika Nusantara Satu, 2024)
Bullying is intentional behavior aimed at causing physical or mental harm, often seen as a form of violence. In schools, bullying is common, with many students reporting incidents to teachers and parents. Data from the Indonesian Child Protection Commission (2020) indicates that there were 1,567 cases of bullying in educational settings, including 76 cases where children were victims and 12 cases where they were perpetrators. This community service initiative sought to assess students' understanding of bullying in Balocci, focusing on increasing awareness of positive behaviors to prevent all types of bullying, including physical, verbal, social, and cyberbullying. The activity took place on October 14, 2023, at SMP Negeri 2 Balocci, Pangkep Regency, South Sulawesi. It used a combination of lecture and educational game methods, specifically the Muslim Children's Quartet Cards. The lecture provided an overview of bullying’s definition, types, causes, impacts, and prevention strategies through a PowerPoint presentation. Meanwhile, the quartet card game, a new method for bullying prevention, added an interactive component. Results showed an increase in participants' knowledge on bullying prevention, with scores rising from 75% to 80% post-intervention. This program suggests establishing a school complaint center involving staff and students to further prevent bullying.